Efficient Stripmap-Mode SAR Raw Data Simulation Including Platform Angular Deviations - Dogan, Ozan; Kartal, Mesut (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The radiometric performance of high-resolution synthetic aperture radar systems under degrading conditions such as the unintentional angular motion of the platform can only be analyzed and evaluated by modeling the whole imaging system through simulation. The raw data generation in the time domain achieves a realistic simulation procedure but, on the contrary, is time inefficient. The frequency-domain approach promises computational efficiency; however, it lacks the consideration of the antenna deviations. In this letter, we propose a frequency-domain stripmap-mode raw data generator of an extended scene, taking into consideration the platform angular deviations. The generated raw data are also validated, and the corresponding radiometric degradation is analyzed.